Geotechnical, geological and geophysical study for the location of the piques dam – San Juan de Bigote – Morropón – Piura - Sanchez Espinoza, Bella Susy (2023)
In the investigation, studies of geotechnics, geology, geophysics, data processing and interpretation of the information obtained in situ and laboratory of the location of the dam are carried out. The geological study includes the execution of cartography, mapping, lithostratigraphy, structural and dynamic geomorphology. In geotechnics, four 04 (pits) were drilled in the open, the material was characterized by the SUCS classification, obtaining clayey gravel and well-graded gravel (GC - GW), with ϴ =31.60°, density = 2.07g/cm3 and c = 0.34kg/cm2, the stability analysis was carried out on the most critical slope of the dam, obtaining static values = 1.836 and pseudostatic = 1.102, these meet the conditions of the limit equilibrium method, the geophysical test consists of four seismic refraction lines and 26 vertical electrical drilling tests along the axis of the dam. The research is of the applied type, descriptive design, quantitative approach and with a correlational level, because its purpose is to establish the degree of relationship between the study variables.